Manifestations of national identity in new Kurdish poetry - Hussein, Asst.Prof.Dr. Hiwa Karim (Sulaimani Journal for Humanities, 2025)
Literature, particularly poetry, has long played a crucial role in shaping national identity throughout history. In the late 19th and early 20th centuries, modern Kurdish literature, especially poetry, began to emerge as a powerful expression of national consciousness. We consider Haji Qadir Koyi the pioneer of modern Kurdish poetry, followed by influential poets such as Piramird, Goran, and Sheikh Nuri. This study examines how national identity is manifested in modern Kurdish poetry. During its early development, this poetry carried a profound intellectual and cultural weight, shaped by the suffering and lived realities of the Kurdish people. More than just artistic expression, it became a medium for asserting Kurdish national identity, reflecting the poets' struggle for recognition and cultural preservation. This highlights the broader social and national responsibility of literature, particularly poetry. Our research is divided into two main sections. The first, a theoretical framework, explores key concepts such as identity, nationhood, and the relationship between poetry and national identity. It also traces the origins of modern Kurdish poetry, with a focus on Haji Qadir Koyi as its founding figure. In the second part, we will explore how national values are reflected in modern Kurdish poetry. This includes themes such as honoring martyrs, celebrating Newroz as a national tradition, viewing national and ethnical poetry as tool for uprising and resistance, expressing pride in the Kurdish language as a symbol of identity, conveying messages of unity and solidarity, and raising awareness through poetic expression. The study concludes with key findings, followed by a Harvard-style reference list.
Keywords: Identity; Nation; Modern Poetry; Haji Qadir Koyi; Language; History; Culture